Prevalence and risk factors of hypertension among police personnel of district gwalior- A cross sectional study - Vikrant S Chauhan; Manoj Bansal; Vikash Sharma; Rajesh Gupta (Wolters Kluwer Medknow Publications, 2022)
Context: Hypertension is an emerging public health problem due to its high prevalence and association with cardiovascular and overall morbidity and mortality. Police personnel constitute a special occupational group with exposure to violence and stress at work, which affects their health directly and indirectly. Methodology: A cross-sectional study was conducted to find out the prevalence of hypertension and its relation with respect to police duty profile along with other risk factors among the police personnel of the Gwalior district stationed at various police stations. Results: In total, 402 police personnel were included in the study. Forty (14.7%) participants reported that they had h/o hypertension, while 26 (9.5%) reported that they were diagnosed as hypertensive in recent 1-2 months. As per the findings of our study, 273 (67.91%) participants come out to be hypertensive; among them, 207 (75.8%) were diagnosed in the current study. With increase in hierarchy, more police personnel suffered with hypertension. Conclusions: Long duty hours, higher rank, prolonged service duration, and inappropriate eating habits are the significant factors for the high prevalence of hypertension in police personnel.